Grupo especializado de produtores de abacaxi do município de Cruzeiro do Oeste: o caráter formativo-pedagógico das relações de trabalho entre 2004 e 2015 - Moreira, Pedro Luiz (2016)
The contradictions of the capitalist mode of production get evident in the most varied forms of social inequality. Those, by their turn, have put into more evidence the system limitations to promote mankind's development. Therefore, the overcoming of obstacles that hinder or limit human development depends on the transformation of production social relations. For the transformation of social relations of production it is essential the role of education, with a view to the continuous development of Socialist awareness. According to this perspective, beyond formal education, it is also important non-formal education which occurs in non-formal space, highlighting formative processes that happen in work spaces. Thus, what is inquired is whether work relations which occurs in the GEA (Pineapple Specialized Group) are a possibility of establishing new social relations which could point to the overcoming of capitalist contradictions? The overall objective of the research is to analyze the pedagogical-formative of work relations in the "Pineapple Specialized Group", in the northwest region of the Paraná state, in the city Cruzeiro do Oeste. This analysis track unfolds in four specific objectives; 1) summarize the emergence of capitalist social formation and work relations in Brazil; 2) analyze the macroeconomical context and its implications for Brazil, when the PSG was created; 3) discuss aspects of the relation between work and education using the capitalist production mode as a reference; and 4) systematize the knowledge of pedagogical-formative character in work relations that occur in PSG. We set out the hypothesis that the working relationships that occur in the PSG, points to the possibility of overcoming both the division between manual and intellectual work, as the exercise of power verticality, in the work relation. The methodological path indicated the need of Division of labour in four chapters thus formed: first briefly presents the emergence of capitalist social formation model and its impact on labor relations in Brazil. In the second analysis is about how it happened, within the context of development of capitalism, the insertion of international capital in the development of the economy of the country and the way it is in conditions of the creation of the PSG in the municipality of Cruzeiro do Oeste, Paraná northwestern region. The third chapter makes an approach on the relationship between work and education marked by internal contradictions of capitalist relations of production. In the fourth chapter is made a presentation of the internal regulations regulating labour relations in the PSG, as well as the development of some of its core activities, such as Division, planning and work execution. The results presented in the research allow us to say that the elements that constitute working practices in the PSG, have significant relevance for the training of its members in order to overcome common sense views. They point for a way of conceiving labor relationships that align to the Socialist perspective. According to discussions presented, work at the PSG is distinguished by three significant aspects of importance for the working class. The first relates to the fact that has ensured the survival of workers with relative autonomy. The second, such practices contribute to the formation of a worker who participates in making collective decisions concerning economic processes and work organization. And third, it contributes to the formation of a worker who has a less fragmented knowledge about their work and their output, since that both intellectual and manual work is performed by all workers.